P-doped Ruddlesden-Popper type perovskite Sr3FeCoO7 electrochemical catalyst as well as preparation method and application thereof
By doping phosphorus atoms in Ruddlesden-Popper perovskite Sr3FeCoO7, adjusting the 2p band center of oxygen, and activating lattice oxygen, the problem of slow reaction kinetics in traditional electrocatalysts in OER is solved, and efficient water decomposition is achieved Hydrogen has excellent stability and durability.
Patent Information
- Application Number
- CN202411604828.8
- Authority / Receiving Office
- CN · China
- Patent Type
- Applications(China)
- Current Assignee / Owner
- Filing Date
- 2024-11-12
- Publication Date
- 2025-02-25
AI Technical Summary
Existing electrocatalysts exhibit slow reaction kinetics and poor performance in the anode oxygen evolution reaction (OER). Especially due to the limitations of Sabatier principle and linear scale relationship, traditional catalysts cannot exceed the inherent overpotential threshold of 370mV, which hinders the Progress in the production of hydrogen by decomposition of water.
By doping phosphorus atoms into Ruddlesden-Popper perovskite Sr3FeCoO7, adjusting the 2p band center of oxygen, activate lattice oxygen, and reducing the energy barrier of the OER reaction, transforming the OER mechanism from the traditional adsorbent evolution mechanism (AEM) to crystallization LOM mechanism (LOM).
An ultra-low overpotential of 276mV at a current density of 10mA·cm-2 was achieved, which significantly improved catalytic activity and stability, and was better than the performance of undoped compounds.
Smart Images

Figure CN119506944A_ABST
Abstract
Description
Technical Field
[0001] The present invention belongs to the technical field of electrochemical catalysis, and in particular, relates to a P-doped Ruddlesden-Popper type perovskite Sr3FeCoO7 electrochemical catalyst and a preparation method and application thereof. Background Art
[0002] It is imperative to research and develop safe, clean and renewable energy sources. Among various alternative energy sources, hydrogen stands out due to its abundant availability, high energy density and zero emissions. Electrocatalytic water splitting is a promising method to produce hydrogen from renewable energy. However, the anodic oxygen evolution reaction (OER) is the main bottleneck of water decomposition due to its sluggish reaction kinetics and the poor performance of existing electrocatalysts. Although noble metal electrocatalysts such as RuO2 and IrO2 exhibit excellent OER activity, their scarcity and instability hinder their widespread application. Therefore, the development of abundant transition metal electrocatalysts is crucial to advance large-scale water splitting for hydrogen production.
[0003] Understanding the OER mechanism is crucial for designing better electrocatalysts. Due to the limitations of the Sabatier principle and the linear scaling relationship of key intermediates (such as *O, *OH, and *OOH), catalysts following the traditional adsorbate evolution mechanism (AEM) are usually unable to exceed the intrinsic overpotential threshold of around 370 mV. Therefore, it is crucial to synthesize OER catalysts that can break the linear relationship. Currently, a new OER mechanism involving lattice oxygen has been proposed, which requires the direct formation of O-O bonds through coupling between lattice oxygen and *O. This lattice oxygen mechanism (LOM) can circumvent the inherent limitations of the AEM. Although the LOM pathway may lack thermodynamic stability on the catalyst surface, it allows dynamic lattice oxygen changes during the OER process. Therefore, activating lattice oxygen is crucial for the LOM pathway. Normally, the O 2p band center should move up to the Fermi level (E f ) to enhance the orbital hybridization between the metal d-band and oxygen, thereby strengthening the covalency of the TM-O bond and thus supporting the LOM. Recent advances in OER catalysts have shown that heteroatom doping can effectively tune the binding energy of oxygen intermediates and reduce the energy barrier of the AEM. Summary of the invention
[0004] The purpose of the present invention is to provide a P-doped Ruddlesden-Popper type perovskite Sr3FeCoO7 electrochemical catalyst and its preparation method and application; the present invention utilizes the tunable electronic structure and performance of Ruddlesden-Popper (RP) perovskite Sr3FeCoO7 (SFCO), and dopes heteroatom phosphorus (P) to fill the oxygen vacancies in Sr3FeCoO7 (SFCO-P), thereby regulating the O 2p center, thereby activating the lattice oxygen and reducing the OER reaction energy barrier. Chemical probe analysis shows that the OER mechanism changes from AEM to LOM, which significantly improves the catalytic activity. At a current density of 10 mA cm -2 When , the electrocatalyst has a lower overpotential of 276 mV via the LOM pathway, which is significantly better than the performance of its undoped P compound.
[0005] The purpose of the present invention can be achieved through the following technical solutions:
[0006] A method for preparing a P-doped Ruddlesden-Popper type perovskite Sr3FeCoO7 electrochemical catalyst comprises the following steps:
[0007] (1) Precursor preparation
[0008] Sr(NO3)3·6H2O, Fe(NO3)2·6H2O, Co(NO3)2, citric acid and ethylene glycol were added to deionized water and ultrasonically treated for 30 minutes to obtain a uniform nitrate mixed solution. Subsequently, the mixed solution was heated until a purple sol was formed. The purple sol was dried in an oven to obtain a brown solid, which was the prepared Sr3FeCoO7 precursor.
[0009] (2) Primary pyrolysis
[0010] The precursor obtained in step (1) is placed in a muffle furnace, heated to 500°C in air at a certain heating rate and maintained for 24 hours, then taken out and ground, and then heated to 1000°C for a second time and maintained for several hours. After cooling to room temperature, the product is collected.
[0011] (3) Pyrolysis phosphating
[0012] The pyrolysis product of step (2) and NaH2PO2·H2O are weighed and placed in a tubular furnace, with NaH2PO2·H2O located upstream and Sr3FeCoO7 located downstream. In an inert gas atmosphere, the mixture is treated at 500°C for 3h and fully ground to obtain the electrochemical catalyst.
[0013] Furthermore, in step (1), the usage ratio of Sr(NO3)3·6H2O, Fe(NO3)2·6H2O, Co(NO3)2, citric acid and ethylene glycol is 3mmol:1mmol:1mmol:10mmol:6mL.
[0014] Furthermore, the oven drying conditions in step (1) are: drying in an oven at 100° C. for 2 hours.
[0015] Furthermore, in step (2), the heating rate is 5°C / min; the temperature is raised to 1000°C and maintained for 12 hours.
[0016] Furthermore, in step (3), the molar ratio of the pyrolysis product to NaH2PO2·H2O is 1:5.
[0017] Furthermore, the inert gas in step (3) is argon.
[0018] Another aspect of the present invention provides an electrochemical catalyst prepared by the above preparation method, and use of the electrochemical catalyst in an anodic oxygen evolution reaction (OER) under alkaline conditions.
[0019] Beneficial effects of the present invention:
[0020] The present invention provides a method for preparing an electrochemical catalyst by doping a heteroatom P into a Ruddlesden-Popper perovskite oxide Sr3FeCoO7, and applies the method to an OER catalyst under alkaline conditions. Compared with the prior art, the P atom is introduced into the Ruddlesden-Popper perovskite oxide Sr3FeCoO7 to achieve electron redistribution. The material has a high conductivity at 10 mA cm -2 The ultra-low overpotential of 276 mV under low temperature has excellent stability and durability. The incorporation of heteroatom P shifts the p-band center of oxygen in Sr3FeCoO7 upward, promotes the lattice oxygen mechanism, and accelerates the OER kinetics. The present invention provides a feasible method for developing high-performance Ruddlesden-Popper perovskites for water decomposition. BRIEF DESCRIPTION OF THE DRAWINGS
[0021] The present invention will be further described below in conjunction with the accompanying drawings.
[0022] Figure 1 Schematic diagram of the theoretical calculation of the changes in the O p band center and the metal d band center after P is doped into Sr3FeCoO7;
[0023] Figure 2 is a flow chart of the preparation method of the present invention;
[0024] Figure 3The X-ray diffraction (XRD) comparison diagrams of Example 1, Comparative Examples 1-3, the precursor Sr3FeCoO7 and the standard card;
[0025] Figure 4 The OER performance test data of five catalysts of Example 1, Comparative Examples 1-3, and precursor Sr3FeCoO7 are shown in Figure 2: (a) LSV curve, (b) Tafel slope graph, (c) EIS graph, (d) double layer capacitance, (e) 10 mA·cm -2 (f) The stability and LSV curves before and after the chronopotentiometry were measured.
[0026] Figure 5 (a) SEM image of the precursor Sr3FeCoO7; (b)-(f) are the SEM image, TEM image, HRTEM image, SAED image and element distribution map of Example 1, respectively;
[0027] Figure 6 The pH dependence test graphs of the precursor Sr3FeCoO7 and Example 1, (a) Precursor Sr3FeCoO7; (b) Polarization curve of Example 1 in KOH of different pH; (cd) Precursor Sr3FeCoO7; (de) Polarization curve of Example 1 in 1.0M KOH and TMAOH and the corresponding Tafel slope. DETAILED DESCRIPTION
[0028] The following will be combined with the embodiments of the present invention to clearly and completely describe the technical solutions in the embodiments of the present invention. Obviously, the described embodiments are only part of the embodiments of the present invention, not all of the embodiments. Based on the embodiments of the present invention, all other embodiments obtained by ordinary technicians in this field without creative work are within the scope of protection of the present invention.
[0029] The schematic flow diagram of the preparation method of the present invention is as follows Figure 2 shown.
[0030] Example 1
[0031] 3mmol Sr(NO3)3·6H2O, 1mmol Fe(NO3)2·6H2O, 1mmol Co(NO3)2, 10mmol citric acid and 6mL ethylene glycol were added to 100mL deionized water and ultrasonically treated for 30min to obtain a uniform nitrate mixed solution. Subsequently, the mixed solution was heated until a purple sol was formed. The purple sol was dried in an oven at 100℃ for 2 hours to obtain a brown solid, which was the prepared Sr3FeCoO7 precursor. The obtained precursor was placed in a muffle furnace, heated to 500℃ at a heating rate of 5℃ / min in air and maintained for 24h, then taken out and ground, and then continued to heat up to 1000℃ for a second time and maintained for 12 hours. After cooling to room temperature, the product was collected.
[0032] The collected product and NaH2PO2·H2O were weighed in a molar ratio of 1:5 and placed in a tube furnace, with NaH2PO2·H2O located upstream and Sr3FeCoO7 located downstream. They were heated at 500°C for 3 h in an argon atmosphere. After cooling, the obtained sample was fully ground to obtain the final product, which was recorded as SFCO-P500.
[0033] like Figure 5 (a) is the SEM image of the precursor Sr3FeCoO7; Figure 5 (b)-(f) show the SEM images, TEM images, HRTEM images, SAED images and element distribution diagrams of the product obtained in Example 1;
[0034] Figure 6 The pH dependence test graphs of the precursor Sr3FeCoO7 and Example 1, (a) polarization curves of the precursor Sr3FeCoO7 (b) Example 3 in KOH of different pH values, (cd) polarization curves of the precursor Sr3FeCoO7, (de) Example 3 in 1.0M KOH and TMAOH and the corresponding Tafel slopes.
[0035] Comparative Example 1
[0036] 3mmol Sr(NO3)3·6H2O, 1mmol Fe(NO3)2·6H2O, 1mmol Co(NO3)2, 10mmol citric acid and 6mL ethylene glycol were added to 100mL deionized water and ultrasonically treated for 30min to obtain a uniform nitrate mixed solution. Subsequently, the mixed solution was heated until a purple sol was formed. The purple sol was dried in an oven at 100℃ for 2 hours to obtain a brown solid, which was the prepared Sr3FeCoO7 precursor. The obtained precursor was placed in a muffle furnace, heated to 500℃ at a heating rate of 5℃ / min in air and maintained for 24h, then taken out and ground, and then continued to heat up to 1000℃ for a second time and maintained for 12 hours. After cooling to room temperature, the product was collected.
[0037] The collected product and NaH2PO2·H2O were weighed in a molar ratio of 1:5 and placed in a tube furnace, with NaH2PO2·H2O located upstream and Sr3FeCoO7 located downstream. They were heated at 300°C for 3h in an argon atmosphere. After cooling, the obtained sample was fully ground to obtain the final product, which was recorded as SFCO-P300.
[0038] Comparative Example 2
[0039] 3mmol Sr(NO3)3·6H2O, 1mmol Fe(NO3)2·6H2O, 1mmol Co(NO3)2, 10mmol citric acid and 6mL ethylene glycol were added to 100mL deionized water and ultrasonically treated for 30min to obtain a uniform nitrate mixed solution. Subsequently, the mixed solution was heated until a purple sol was formed. The purple sol was dried in an oven at 100℃ for 2 hours to obtain a brown solid, which was the prepared Sr3FeCoO7 precursor. The obtained precursor was placed in a muffle furnace, heated to 500℃ at a heating rate of 5℃ / min in air and maintained for 24h, then taken out and ground, and then continued to heat up to 1000℃ for a second time and maintained for 12 hours. After cooling to room temperature, the product was collected.
[0040] The collected product and NaH2PO2·H2O were weighed in a molar ratio of 1:5 and placed in a tube furnace, with NaH2PO2·H2O located upstream and Sr3FeCoO7 located downstream. They were heated at 400°C for 3 h in an argon atmosphere. After cooling, the obtained sample was fully ground to obtain the final product, which was recorded as SFCO-P400.
[0041] Comparative Example 3
[0042] 3mmol Sr(NO3)3·6H2O, 1mmol Fe(NO3)2·6H2O, 1mmol Co(NO3)2, 10mmol citric acid and 6mL ethylene glycol were added to 100mL deionized water and ultrasonically treated for 30min to obtain a uniform nitrate mixed solution. Subsequently, the mixed solution was heated until a purple sol was formed. The purple sol was dried in an oven at 100℃ for 2 hours to obtain a brown solid, which was the prepared Sr3FeCoO7 precursor. The obtained precursor was placed in a muffle furnace, heated to 500℃ at a heating rate of 5℃ / min in air and maintained for 24h, then taken out and ground, and then continued to heat up to 1000℃ for a second time and maintained for 12 hours. After cooling to room temperature, the product was collected.
[0043] The collected product and NaH2PO2·H2O were weighed in a molar ratio of 1:5 and placed in a tube furnace, with NaH2PO2·H2O located upstream and Sr3FeCoO7 located downstream. They were heated at 600°C for 3 h in an argon atmosphere. After cooling, the obtained sample was fully ground to obtain the final product, which was recorded as SFCO-P600.
[0044] like Figure 1 The figure shows the change of O p band center and metal d band center after P doping into Sr3FeCoO7 according to theoretical calculation; Figure 3 It is a comparison chart of X-ray diffraction (XRD) of Example 1, Comparative Examples 1-3, precursor Sr3FeCoO7 and standard card.
[0045] The catalyst synthesized by the catalyst preparation method provided by the present invention has good OER catalytic performance and can be actually applied to electrolyze water to produce hydrogen. The specific application is described in detail through the following cases:
[0046] (1) Pretreatment of working electrode
[0047] The working electrode used was a straight glassy carbon electrode (GCE, 3 mm in diameter), which was carefully polished on the suede surface with micron-grade Al2O3 powder. Each polishing time was 5 min. The polished glassy carbon electrode was rinsed clean of the polishing powder on the surface with deionized water, then cleaned with ethanol, and finally dried under a dust-free infrared lamp.
[0048] (2) Modified glassy carbon electrode
[0049] 10 mg of each of the five catalysts SFCO-P500, SFCO-P300, SFCO-P400, SFCO-P600 and the precursor Sr3FeCoO7 prepared in Example 1 and Comparative Examples 1-3 were dispersed in 70 μL of a mixed solution of Nafion (5wt%) and 1 mL of anhydrous ethanol, and then dispersed evenly by ultrasonic dispersion to obtain dispersants of five different catalysts. 3 μL of the catalyst dispersion was dripped onto a polished glassy carbon electrode three times, and dried under an infrared lamp to obtain a catalyst-modified electrode.
[0050] (3) Electrochemical test
[0051] Electrochemical tests were performed on the electrodes modified with five catalysts to compare their OER catalytic performance and analyze the effect of different heating temperatures on the OER catalytic performance of the catalysts. The electrochemical test used a classic three-electrode system, in which the catalyst-modified straight glassy carbon electrode was the working electrode, the carbon rod was the counter electrode, and the Hg / HgO electrode was the reference electrode. 1.0 mol L -1 KOH was used as the electrolyte to carry out OER performance tests under alkaline conditions, including linear sweep voltammetry (LSV), Tafel slope, cyclic voltammetry (CV), electrochemical impedance spectroscopy (EIS) and stability tests.
[0052] The OER performance test results of different catalysts in this application example are as follows: Figure 4 shown. Figure 4 a is the LSV test curve of SFCO-P300, SFCO-P400, SFCO-P500, SFCO-P600 and precursor Sr3FeCoO7 catalyst, from which the overpotential, mass activity and Tafel slope are calculated. Figure 4 b Comparison of the Tafel slopes of SFCO-P300, SFCO-P400, SFCO-P500, SFCO-P600 and the precursor Sr3FeCoO7 catalyst prepared by this method. -2 At a current density of 1.3 Å, the overpotential of SFCO-P500 is 276 mV, which is much lower than that of SFCO-P300, SFCO-P400, SFCO-P600, precursor Sr3FeCoO7 and IrO2. The Tafel slope of SFCO-P500 is 92.84 mV·dec -1 , much lower than SFCO-P300, SFCO-P400, SFCO-P600, precursor Sr3FeCoO7 and IrO2. Figure 4 From the EIS spectrum of c, it can be seen that SFCO-P500 has the smallest charge transfer resistance. Figure 4d. The double-layer capacitance is calculated through CV test data. By comparison, it can be seen that the double-layer capacitance of SFCO-P500 is the highest. Figure 4 e Comprehensive comparison of the -2 The performance of SFCO-P300, SFCO-P400, SFCO-P500, SFCO-P600 and precursor Sr3FeCoO7 at a current density of 1.5 %. The stability of the catalyst was tested for 100 hours, and the curve is as follows: Figure 4 f, indicating that it has good stability.
[0053] The above specific implementation method part specifically introduces the analytical method involved in the present invention. It should be noted that the above introduction is only to help those skilled in the art better understand the method and ideas of the present invention, rather than limiting the relevant content. Without departing from the principle of the present invention, those skilled in the art may also make appropriate adjustments or modifications to the present invention, and the above adjustments and modifications shall also fall within the scope of protection of the present invention.
Claims
1. A method for preparing a P-doped Ruddlesden-Popper type perovskite Sr3FeCoO7 electrochemical catalyst, characterized in that: The following steps are involved: (1) Precursor preparation Sr(NO3)3·6H2O, Fe(NO3)2·6H2O, Co(NO3)2, citric acid and ethylene glycol were added to deionized water and subjected to ultrasonic treatment for 30 minutes to obtain a uniform nitrate mixed solution; then, the mixed solution was heated until a purple sol was formed, and the purple sol was dried in an oven to obtain a brown solid, which was the prepared Sr3FeCoO7 precursor; (2) Primary pyrolysis The precursor obtained in step (1) is placed in a muffle furnace, heated to 500° C. in air at a certain heating rate and maintained for 24 hours, then taken out and ground, and then heated to 1000° C. for a second time and maintained for several hours, and after cooling to room temperature, the product is collected; (3) Pyrolysis phosphating The pyrolysis product of step (2) and NaH2PO2·H2O are weighed and placed in a tubular furnace, with NaH2PO2·H2O located upstream and Sr3FeCoO7 located downstream. In an inert gas atmosphere, the mixture is treated at 500°C for 3h and fully ground to obtain the electrochemical catalyst.
2. The method for preparing the P-doped Ruddlesden-Popper type perovskite Sr3FeCoO7 electrochemical catalyst according to claim 1, characterized in that: In step (1), the dosage ratio of Sr(NO3)3·6H2O, Fe(NO3)2·6H2O, Co(NO3)2, citric acid and ethylene glycol is 3mmol:1mmol:1mmol:10mmol:6mL.
3. The method for preparing the P-doped Ruddlesden-Popper type perovskite Sr3FeCoO7 electrochemical catalyst according to claim 1, characterized in that: The oven drying conditions in step (1) are: drying in an oven at 100° C. for 2 hours.
4. The method for preparing the P-doped Ruddlesden-Popper type perovskite Sr3FeCoO7 electrochemical catalyst according to claim 1, characterized in that: In step (2), the heating rate is 5°C / min; the temperature is raised to 1000°C and maintained for 12 hours.
5. The method for preparing the P-doped Ruddlesden-Popper type perovskite Sr3FeCoO7 electrochemical catalyst according to claim 1, characterized in that: In step (3), the molar ratio of the pyrolysis product to NaH2PO2·H2O is 1:
5.
6. The method for preparing the P-doped Ruddlesden-Popper type perovskite Sr3FeCoO7 electrochemical catalyst according to claim 1, characterized in that: The inert gas in step (3) is argon.
7. P-doped Ruddlesden-Popper type perovskite Sr3FeCoO7 electrochemical catalyst, characterized in that Prepared according to the preparation method according to any one of claims 1 to 6.
8. Use of the P-doped Ruddlesden-Popper type perovskite Sr3FeCoO7 electrochemical catalyst according to claim 7 in an anodic oxygen evolution reaction under alkaline conditions.
Citation Information
Patent Citations
Phosphor-doped dual-function perovskite-based catalyst and preparation method thereof
CN107486212A
Layered perovskite-type oxide, preparation method and use thereof in the oxygen evolution reaction electrocatalyst
CN108579751A
Preparation method and application of CO2 hydrogenation catalyst
CN112076755A